Mangrove Ecosystem Ecology and Function - Sharma, Sahadev (IntechOpen, 2018)
Mangrove Ecosystem Ecology and Function deals with several aspects of mangrove science, as well as conservation, management, and related policies. The book is divided into six sections and structured into 10 chapters. The first section discusses mangrove ecology, structure, and function; the second section explains mangrove physiology related to salt accumulation; the third section focuses on mangrove polychaetes; the fourth section talks about the bioprospect of mangrove microbes; the fifth section discusses soil geochemistry; and the sixth section elucidates mangrove management and conservation. Researchers from different countries and fields of mangrove ecosystem exploration have contributed their findings. This book would be an ideal source of scientific information to graduate students, advanced students, researchers, scientists, and stakeholders involved in mangrove ecosystem research.